Drawing the triangle: how coaches manage ambiguities inherited in executive coaching - Pliopas, Ana Luísa Villares da Silva Vieira (2017)
Executive coaching is a common leadership development intervention whose complexity is underestimated. The triangular relationships between coachee, coach, and organization give rise to conflicting interests (Fatien-Diochon, 2012). This study examines how coaches perceive triangular relationships and reflect on conflicts of interest and ethical issues. During semi-structured interviews, nine coaches drew their interpretations of how triangular relationships unfold in executive coaching processes. Coaches’ explanations were categorized into three groups. There are coaches who understand executive coaching as a harmonious and congruent process, called naïve; some coaches rely on the coaching process to deal with conflicts of interest, and we called them procedural. Other coaches are skeptical when dealing with conflict of interests in triangular relationships, and were called suspicious. In order to support coaches facing ethical dilemmas that may be present in triangular relationships in the executive coaching process, the ethics of the profession perspective developed for the educational sector by Shapiro and Stefkovich (2016) was adapted and integrated into Carroll and Shaw’s (2013) ethical maturity perspective. This adapted model offers coaches an integrative and dynamic view to foster their development and ethical maturity. © 2017, ANPAD - Associacao Nacional de Pos-Graduacao e Pesquisa em Administracao. All rights reserved.